1. Start by solving one of the equations for one variable in terms of the other variable. In this case, you could solve the second equation for x in terms of y:
x = 2y + 11
2. Substitute the expression for x from step 1 into the other equation.
-7(2y + 11) - 2y = -13
3. Simplify and solve for y.
-14y - 77 - 2y = -13
-16y - 77 = -13
-16y = 64
y = -4
4. Substitute the value of y from step 3 into one of the original equations to solve for x. Let's use the second equation:
x - 2(-4) = 11
x + 8 = 11
x = 3
5. The solution to the system of equations is x = 3, y = -4.
Put the steps in order that are used to solve the following systems of equations by substitution. −7x−2y=−13 x−2y=11
1 answer